Policy diffusion in space and time: The case of charter schools in California school districts - Rincke, Johannes (Regional Science and Urban Economics, 2007)
The literature on policy diffusion and emulation has gathered descriptive evidence on the behavior of state and local governments in the adoption of policy innovations, but structural evidence is largely missing. Using spatial econometric models for limited dependent variables, this paper presents evidence on the diffusion of charter schools among California school districts. Strong positive spatial correlation either in the districts' predisposition towards the establishment of charter schools or between the districts' predisposition and lagged adoptions of neighbors is found. The results support the view that in decentralized systems of government the diffusion of new political technologies is driven by horizontal interactions among jurisdictions.
WiSo-Import:2015-03-26:1713
Keywords: policy innovation; policy diffusion; spatial correlation; charter schools